Three new species of the genus Ocychinus (Coleoptera, Staphylinidae) from China - Zhao, Xin; Tang, Liang (Zootaxa, 2020)
Three new species of the genus Ocychinus Smetana, 2003 from China are described: O. motuoensis sp. n. and O. smetanai sp. n. both from Xizang and O. huanghaoi sp. n. from Sichuan. Diagnostic characters for new species are illustrated. Habitus photos of 16 Ocychinus species are given and a key to species of Ocychinus is provided.